A comprehensive review on impacts of COVID‐19 in food preservation and cold chain: An approach towards implementing green energy technologies. Issue 5 (8th March 2022) - Edwin, M.; Nair, M. Saranya; Sekhar, S. Joseph
Abstract: Technology plays a crucial role in fighting COVID‐19 pandemic. The COVID‐19 pandemic impacts all facets of human life, including food preservation and supply chain. The changes in the food processing and preservation brings changes to the global food choice. In the age of the COVID‐19 pandemic scare, the present article explores the framework for food security. It offers insights into food security with a focus on renewable energy to help rural farmers, besides, exploring the possibility of the diffusion of COVID‐19 via food chain. This article indicates that the implementation of stand‐alone and hybrid renewable energy systems is relatively fresh in food processing, preservation, and transportation chain. Green food preservation may be a revolutionary idea to address the challenges of the future to secure both producers and customers, besides, to improve the attractiveness of the ecological, economic, and creative sectors. This study reveals that the transformation can be achieved from a technological and economic point of view with the key steps to fulfill this goal in a cost‐effective manner. The observation also shows a suitable methodology to identify the best energy, economic and environmental scenario towards fulfilling the energy needs in isolated areas.